Menyinergikan Aturan Prudensial Dan Aturan Kepatuhan Syariah Pada Perbankan Syariah Di Indonesia - Agus Triyanta (Fakultas Hukum Universitas Islam Indonesia, 2019)
Besidesbeing generally bound by prudential principles in banking regulations, Islamic banking in Indonesia is also bound by sharia principles. In reality, there are several contradictions between these two jurisdictions (conventional banking and Islamic banking). This article aims to discuss why the contradictions between these two jurisdictions can occur. Furthermore, how the possibilities are to make harmony or adjustment among the various different elements, so that these two different jurisdictions can synergistically play a role in driving the development of Islamic banking in Indonesia. The research method in this article is normative legal research with a qualitative analysis model. The conclusion of this article showed that the set of regulations related to the prudential principle of banking in two banking models (conventional and sharia) in fact were the same. It was because this regulation related to banking prudential was originally designed for conventional banking, and, when applied to Islamic banking, various adjustments were needed, for example in the collateral case. This article recommends that sharia-based prudential principles should be immediately integrated into the regulation of banking prudential principles in general to prevent any problems arose from the application of Islamic banking.